Comparison between Solar-Powered and Diesel-Driven Water Pumping Systems for Oil-Palm Irrigation Plantations - Mohamed Eldirdiri Ali Khalfallah; Hussin, Siti Maherah; Norzanah Rosmin; Norazliani Md Sapari; Madihah Md Rasid; Amirjan Nawabjan (ELEKTRIKA- Journal of Electrical Engineering, 2024)
This paper presents a comprehensive comparative study between solar-powered and diesel-driven water pumping systems for irrigating oil palm plantations in the dry regions of Malaysia. The study aims to address the need for sustainable and efficient water pumping systems in these areas, considering the costs and environmental impact associated with traditional diesel-driven systems. The research specifically focuses on evaluating the feasibility and effectiveness of solar-powered systems as an alternative to diesel-driven systems in the context of Malaysian oil palm plantations. The study employs the HOMER software to evaluate the feasibility and performance of solar-powered water pumping systems in comparison to conventional diesel-driven systems. The research methodology involves collecting data on oil-palm plantations in dry regions and obtaining relevant meteorological data. Subsequently, solar-powered water pumping systems are modeled and simulated using the HOMER software. A comparative analysis is then conducted, considering factors of electrical and economic performances, to evaluate the feasibility and benefits of solar energy for irrigation in Malaysian oil palm plantations. The findings of the study indicate that the configurations of the system without a battery is the most satisfactory, as it demonstrates decent electrical generation, and economic attractiveness with an internal rate of return (IRR) of 17% and a payback period of 5.72 years. Implementing this configuration of the solar-powered water pumping system offers various advantages, including providing adequate water for boosting plantation production, enhancing sustainability, offering environmental benefits, achieving cost savings, and ensuring economic viability. These findings can assist decision-makers in considering the implementation of solar-powered irrigation systems in Malaysian oil palm plantations.